2023
DOI: 10.1007/s40259-023-00629-y
|View full text |Cite
|
Sign up to set email alerts
|

AAV-Based Strategies for Treatment of Retinal and Choroidal Vascular Diseases: Advances in Age-Related Macular Degeneration and Diabetic Retinopathy Therapies

Brenda F. M. Castro,
Jason C. Steel,
Christopher J. Layton

Abstract: Age-related macular degeneration (AMD) and diabetic retinopathy (DR) are vascular diseases with high prevalence, ranking among the leading causes of blindness and vision loss worldwide. Despite being effective, current treatments for AMD and DR are burdensome for patients and clinicians, resulting in suboptimal compliance and real risk of vision loss. Thus, there is an unmet need for long-lasting alternatives with improved safety and efficacy. Adeno-associated virus (AAV) is the leading vector for ocular gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 123 publications
0
2
0
Order By: Relevance
“…Promisingly, studies have showcased the potential of gene therapy in delaying or preventing retinal cell death, and potentially halting the progression of DR. For example, a gene therapy named AAV2-sFLT01 gene therapy, currently in clinical trials, seeks to block VEGF signaling and inhibit the formation of new blood vessels and retinal edema. By introducing a gene encoding this effect into the retina, this therapy aims to enhance the retinal neuron survival [227,228]. In the realm of the clinical trials testing gene therapy in vascular ocular disorders, important differences were observed in the INFINITY trial (NCT04418427), where the patients affected by diabetic macular edema and wet AMD treated with the AAV2.7m8 encoding aflibercept (ADVM-022) at the same dose ultimately displayed dose-limiting toxicity in DR, while encouraging results were reported in AMD, underscoring the detrimental impact of the diabetic condition on the ocular safety of AAV therapies [228,229].…”
Section: Gene and Cell Therapy Advancementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Promisingly, studies have showcased the potential of gene therapy in delaying or preventing retinal cell death, and potentially halting the progression of DR. For example, a gene therapy named AAV2-sFLT01 gene therapy, currently in clinical trials, seeks to block VEGF signaling and inhibit the formation of new blood vessels and retinal edema. By introducing a gene encoding this effect into the retina, this therapy aims to enhance the retinal neuron survival [227,228]. In the realm of the clinical trials testing gene therapy in vascular ocular disorders, important differences were observed in the INFINITY trial (NCT04418427), where the patients affected by diabetic macular edema and wet AMD treated with the AAV2.7m8 encoding aflibercept (ADVM-022) at the same dose ultimately displayed dose-limiting toxicity in DR, while encouraging results were reported in AMD, underscoring the detrimental impact of the diabetic condition on the ocular safety of AAV therapies [228,229].…”
Section: Gene and Cell Therapy Advancementsmentioning
confidence: 99%
“…By introducing a gene encoding this effect into the retina, this therapy aims to enhance the retinal neuron survival [227,228]. In the realm of the clinical trials testing gene therapy in vascular ocular disorders, important differences were observed in the INFINITY trial (NCT04418427), where the patients affected by diabetic macular edema and wet AMD treated with the AAV2.7m8 encoding aflibercept (ADVM-022) at the same dose ultimately displayed dose-limiting toxicity in DR, while encouraging results were reported in AMD, underscoring the detrimental impact of the diabetic condition on the ocular safety of AAV therapies [228,229].…”
Section: Gene and Cell Therapy Advancementsmentioning
confidence: 99%
See 1 more Smart Citation
“… 26 ). Although other approaches can undoubtedly bring benefits to glaucoma and uveitis patients, AAV stands out as a promising technology given the possibility of optimisation of the delivery and expression methods, including regulation, targeting, specificity and multi-acting, in addition to a scalable manufacturing process (Refs 27 , 28 ). These distinctive features underscore the potential of AAV to address challenges associated with the management of prevalent, chronic, multifactorial and complex disorders (Ref.…”
Section: Introductionmentioning
confidence: 99%
“…These distinctive features underscore the potential of AAV to address challenges associated with the management of prevalent, chronic, multifactorial and complex disorders (Ref. 27 ).…”
Section: Introductionmentioning
confidence: 99%